Stem Cell Therapy for Spinal Cord Injury - Huang, Liyi; Fu, Chenying; Xiong, Feng; He, Chengqi; Wei, Quan (Cell transplantation, 2021)
Traumatic spinal cord injury (SCI) results in direct and indirect damage to neural tissues, which results in motor and sensory dysfunction, dystonia, and pathological reflex that ultimately lead to paraplegia or tetraplegia. A loss of cells, axon regeneration failure, and time-sensitive pathophysiology make tissue repair difficult. Despite various medical developments, there are currently no effective regenerative treatments. Stem cell therapy is a promising treatment for SCI due to its multiple targets and reactivity benefits. The present review focuses on SCI stem cell therapy, including bone marrow mesenchymal stem cells, umbilical mesenchymal stem cells, adipose-derived mesenchymal stem cells, neural stem cells, neural progenitor cells, embryonic stem cells, induced pluripotent stem cells, and extracellular vesicles. Each cell type targets certain features of SCI pathology and shows therapeutic effects via cell replacement, nutritional support, scaffolds, and immunomodulation mechanisms. However, many preclinical studies and a growing number of clinical trials found that single-cell treatments had only limited benefits for SCI. SCI damage is multifaceted, and there is a growing consensus that a combined treatment is needed.